Frequency of sports dreams and dreams about politics: an online study - Noveski, Alina; Schredl, Michael; Göritz, Anja (International journal of dream research, 2016)
Many recent studies supported the continuity hypothesis of dreaming which suggests that dream content reflects waking life experiences. This study investigated factors that affect the frequency of sport and politics dreams. The online survey (N=2929 German speaking participants) showed a prevalence of about 6% sport dreams and 4% politics dreams. Results indicated that younger and male participants dreamed more often about sport and politics. Furthermore, higher education was positively correlated with a higher frequency of politics dreams. Moreover, a positive correlation between lucid dream recall frequency and sport dreams was found. Further research is needed to corroborate the present findings using dream diaries to minimize the bias of the retrospective estimates. In addition, the political and sport-related activities of the participants during the day should be assessed in order to correlate waking variables with frequencies of the dream topics directly. These studies might help to further understand the continuity between dream content and waking life experiences.